Modified PVDF (polyvinylidene fluoride) membrane as well as preparation method and application thereof

By introducing NH2/Cu+ composite materials into PVDF membranes, the problems of hydrophobicity and cuprous ion instability on the surface of traditional PVDF membranes are solved, the hydrophilicity and pollution resistance of the membrane are improved, and efficient water quality optimization and long-term use are achieved. performance.

CN119258815AInactive Publication Date: 2025-01-07东晟环保科技集团(安徽)股份有限公司
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411683236.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PVDF membranes have strong surface hydrophobicity in water treatment, resulting in severe adsorption of pollutants, and copper ions are unstable in the membrane, making it difficult to achieve efficient water quality optimization.

Method used

By adding glucosamine and reducing agent to the copper saline solution, NH2/Cu+ composite material is generated, mixed with CNC cellulose nanoparticles, forming CNC-NH2/Cu+ composite material, which is uniformly bound to the surface of the PVDF membrane to improve its hydrophilicity and antibacteriality and antibacteriality and a modified film was prepared by phase conversion method.

Benefits of technology

It significantly improves the film's anti-pollution and durability, enhances the efficiency of removing trace pollutants, extends the service life of the film, and is suitable for the treatment of highly polluted water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258815A_ABST
    Figure CN119258815A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of PVDF membranes, and particularly discloses a modified PVDF membrane and a preparation method and application thereof.The preparation method comprises the steps that after glucosamine is added into a copper salt aqueous solution, the pH value of mixed liquid is adjusted to be 8-10; then dropwise adding a reducing agent, and carrying out reduction reaction to obtain an NH2 / Cu < + > composite material; uniformly mixing the composite material and CNC to obtain a CNC-NH2 / Cu < + > mixture; adding PVDF particles into a PEG solution, and uniformly stirring to obtain a PVDF membrane solution; adding the mixture into a PVDF membrane solution, carrying out ultrasonic dispersion, and then heating and stirring to obtain a membrane casting solution; and coating the membrane casting solution with a membrane, and carrying out phase inversion in pure water to obtain the modified PVDF membrane. The CNC-NH2 / Cu < + > mixture is added, so that the surface hydrophilicity of the membrane is improved, and the removal efficiency of the membrane on trace pollutants is improved; the adsorption of hydrophobic pollutants is reduced, the membrane pollution is obviously reduced, and the service life of the membrane is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVDF membranes, and in particular relates to a modified PVDF membrane and a preparation method and application thereof. Background Art

[0002] As environmental pollution becomes increasingly serious, especially when treating wastewater from anaerobic reactors, we often face challenges of high microbial concentration and complex pollution components. Therefore, developing high-performance membrane materials to improve water treatment efficiency and reduce membrane fouling has become a research hotspot.

[0003] In recent years, polyvinylidene fluoride (PVDF) membranes have been widely used in water treatment, wastewater purification, chemical separation and other fields due to their excellent chemical stability, mechanical strength and heat resistance. However, due to the strong surface hydrophobicity, traditional PVDF membranes have a low retention rate for various components in sewage and are easy to adsorb pollutants, resulting in serious membrane pollution; this results in high levels of organic carbon and other substances in the effluent of the reaction system, which is not conducive to water quality optimization. For this reason, people often improve their hydrophilicity and anti-pollution properties by surface modification or composite material doping to enhance the flux and durability of PVDF membranes. For example, CNC (nanocellulose) modified PVDF membranes are currently used, which have good performance in water flux, but do not have certain anti-pollution and antibacterial properties, and it is difficult to achieve further water quality optimization in practical applications. There are also methods that use metal ions (such as Cu + ) modified. Although the modified PVDF membrane has certain antibacterial properties, its ionic valence makes it easy to oxidize, so it is difficult to exist stably in the PVDF membrane. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a modified PVDF membrane and a preparation method and application thereof.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a modified PVDF membrane comprises the following steps:

[0007] (1) After adding glucosamine to the copper salt aqueous solution, the pH value of the mixed solution is adjusted to 8-10; then a reducing agent is added dropwise to perform a reduction reaction to obtain NH2 / Cu + Composite materials;

[0008] (2) NH2 / Cu + The composite material and CNC are mixed evenly to obtain CNC-NH2 / Cu + mixture;

[0009] (3) adding PVDF particles into PEG solution and stirring evenly to obtain PVDF membrane solution;

[0010] (4) CNC-NH2 / Cu + The mixture is added into PVDF membrane liquid for ultrasonic dispersion, and then heated and stirred to obtain a casting liquid; the casting liquid is coated with a film and placed in pure water for phase conversion to obtain a modified PVDF membrane.

[0011] In a further embodiment, in step (1), the copper salt aqueous solution includes copper nitrate, copper chloride or copper acetate aqueous solution, and its concentration is 0.02-0.08 mol / L;

[0012] The reducing agent is L-ascorbic acid solution;

[0013] The pH value of the mixed solution is adjusted using NaOH, KOH or Na2CO3.

[0014] In a further embodiment, in step (1), the molar ratio of the copper salt aqueous solution, glucosamine and reducing agent is 200:20:1.

[0015] In a further embodiment, in step (2), the NH2 / Cu + The mixed mass ratio of composite materials and CNC is 1:1.

[0016] In a further embodiment, in step (3), the PEG solution is obtained by adding PEG (polyethylene glycol) to NMP (N-methylpyrrolidone), wherein PEG accounts for 2-4% of the total mass of the PVDF membrane solution.

[0017] In a further embodiment, in step (4), the heating and stirring is performed at a temperature of 50-70° C. and for a time of 20-28 hours.

[0018] The CNC-NH2 / Cu + The mass ratio of the mixture to the mass ratio of PVDF is 0.2-2.0%.

[0019] The second object of the present invention is to provide a modified PVDF membrane prepared by the above preparation method.

[0020] The third object of the present invention is to provide the application of the modified PVDF membrane as an ultrafiltration membrane in an AnMBR reactor for sewage filtration.

[0021] The present invention solves the problems of poor stability of cuprous ions, insufficient dispersibility of CNC cellulose nanoparticles and difficulty in controlling interfacial polymerization conditions in the preparation process of PVDF membranes. That is, the present invention introduces amino groups into the PVDF membrane to form a stable complex of cuprous ions, thereby improving its uniform distribution and reaction activity in the membrane material. The presence of cuprous ions not only helps to improve the antibacterial properties of the membrane, but also helps to improve the hydrophilicity of the membrane surface. In addition, CNC (nanocellulose) as a dopant can significantly enhance the hydrophilicity of the membrane, reduce the adhesion of dirt on the membrane surface, thereby reducing the membrane pollution effect and improving the long-term use performance of the membrane.

[0022] Therefore, the present invention will CNC-NH2 / Cu + The composite material is evenly bonded to the surface of the PVDF membrane, giving it excellent pollution resistance and efficient separation performance in the AnMBR wastewater treatment process.

[0023] The present invention has the following beneficial effects:

[0024] (1) The pH value of the alkali solution is adjusted to 8-10, thereby providing suitable reaction conditions to promote the Cu 2+ Reduction to Cu + , without causing precipitation of copper hydroxide and while also avoiding the production of unwanted by-products.

[0025] (2) The present invention uses a reducing agent to reduce Cu 2+ Reduction to Cu + , and then glucosamine is added to stabilize the cuprous ions, inhibit their oxidation tendency, keep the cuprous ions active during the preparation process, and ensure their lasting effect in the membrane structure.

[0026] (3) The present invention combines CNC with NH2 / Cu + The composite material is mixed to combine CNC with cuprous ions, which improves the hydrophilicity of the membrane surface, reduces the adsorption of hydrophobic pollutants, significantly reduces membrane fouling, and extends the service life of the membrane.

[0027] (4) The present invention adopts interfacial polymerization by phase inversion method to prepare modified PVDF membrane, optimizes the membrane surface structure, improves its removal efficiency of trace pollutants, and shows good performance in the treatment of industrial wastewater and high-concentration organic wastewater, and is particularly suitable for the treatment of highly polluted water in anaerobic bioreactors. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of water flux of membranes prepared in Examples 1-5 and Comparative Example 1;

[0029] Figure 2 The rejection rate of the membranes prepared in Example 2 and Comparative Example 1 for AnMBR water;

[0030] Figure 3 The normalized flux diagram of the membranes prepared in Example 2 and Comparative Example 1;

[0031] Figure 4 It is the flux recovery ratio of the membranes prepared in Example 2 and Comparative Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific examples, but the essence of the present invention is not limited to the following examples. The methods are conventional methods unless otherwise specified, and the materials can be obtained from public commercial channels unless otherwise specified. Those skilled in the art should know that any simple transformation or substitution based on the essence of the present invention belongs to the protection scope claimed by the present invention.

[0033] The organic pollutants in the present invention refer to tetracycline, bisphenol A, rhodamine B, perfluorooctanoic acid, etc., and the persulfates include potassium persulfate, sodium persulfate, and ammonium persulfate. In the following embodiments, the organic pollutant is tetracycline, and the persulfate is potassium persulfate.

[0034] Embodiment 1:

[0035] A method for preparing a modified PVDF membrane comprises the following steps:

[0036] (1) Add 1.2 g of copper nitrate (CuN2O6·2.5H2O) to 100 ml of pure water and stir at 200 r / min until completely dissolved to obtain a 0.05 mol / L copper salt aqueous solution;

[0037] Then add 0.1 mol / L glucosamine (C6H 13 NO5) 5ml to form a glucosamine-nitric acid mixed solution, add 0.5mol / L NaOH solution under stirring to adjust the pH of the mixed solution to 10; then add 0.005mol / L reducing agent L-ascorbic acid solution 5ml to carry out reduction reaction, let it stand, take the precipitate, wash and dry it to obtain NH2 / Cu + Composite materials;

[0038] The washing process was to first use anhydrous ethanol to centrifuge at a speed of 8000r / min for 10 minutes, then pour out the supernatant, add anhydrous ethanol again for washing (repeat 3 times), and then wash with pure water 3 times under the same conditions. After washing, let it stand for 30 minutes, pour out the excess liquid and put it into a vacuum drying oven at 40℃ for 12 hours to obtain NH2 / Cu + Composite materials.

[0039] (2) NH2 / Cu +The composite material and CNC were mixed uniformly in a mass ratio of 1:1 to obtain CNC-NH2 / Cu + mixture;

[0040] (3) Add 12.8 g of PVDF particles into the PEG solution and stir evenly to obtain a PVDF membrane solution;

[0041] The PEG solution was prepared by adding 3.2 g of PEG (polyethylene glycol) to 83.92 g of NMP (N-methylpyrrolidone);

[0042] (4) 0.0256 g CNC-NH2 / Cu + The mixture was added into the above PVDF membrane solution for ultrasonic dispersion, wherein CNC-NH2 / Cu + The mixture accounts for 0.2% of PVDF by mass, and then heated to 60°C and stirred for 24 hours to obtain a casting solution; the casting solution is coated on a glass plate, wherein the coating is performed using an adjustable coating device, and the flow thickness of the film is controlled by adjusting the liquid discharge speed of the adjustable coating device. The coating thickness in this embodiment is 200um. Then it is placed in pure water for phase inversion to obtain a modified PVDF membrane (0.2wt% CNC-NH2 / Cu + -PVDF).

[0043] Embodiment 2:

[0044] Same as Example 1, except that CNC-NH2 / Cu is added in step (4). + The amount of the mixture is different, and the composition of the casting solution is as follows:

[0045] PVDF 12.8g, PEG 3.2g, NMP 83.92g, CNC-NH2 / Cu + Mixture 0.0768g, then CNC-NH2 / Cu + The mass percentage of the mixture in PVDF is 0.6%; the prepared membrane is recorded as 0.6wt% CNC-NH2 / Cu + -PVDF.

[0046] Embodiment 3:

[0047] Same as Example 1, except that CNC-NH2 / Cu is added in step (4). + The amount of the mixture is different, and the composition of the casting solution is as follows:

[0048] PVDF 12.8g, PEG 3.2g, NMP 83.87g, CNC-NH2 / Cu + Mixture 0.1280g, then CNC-NH2 / Cu +The mass percentage of the mixture in PVDF is 1%; the prepared membrane is recorded as 1.0wt% CNC-NH2 / Cu + -PVDF.

[0049] Embodiment 4:

[0050] (1) Add 1.1 g of copper chloride to 100 ml of pure water and stir at 200 r / min until completely dissolved to obtain a 0.08 mol / L copper salt aqueous solution;

[0051] Then add 0.1 mol / L glucosamine (C6H 13 NO5) 8ml to form a glucosamine-nitric acid mixed solution, add 0.5mol / L Na2CO3 solution under stirring to adjust the pH of the mixed solution to 9; then add 0.005mol / L reducing agent L-ascorbic acid solution 8ml to carry out reduction reaction, let it stand, take the precipitate, wash and dry it to obtain NH2 / Cu + Composite materials;

[0052] The washing process was to first use anhydrous ethanol to centrifuge at a speed of 8000r / min for 10 minutes, then pour out the supernatant, add anhydrous ethanol again for washing (repeat 3 times), and then wash with pure water 3 times under the same conditions. After washing, let it stand for 30 minutes, pour out the excess liquid and put it into a vacuum drying oven at 40℃ for 12 hours to obtain NH2 / Cu + Composite materials.

[0053] (2) NH2 / Cu + The composite material and CNC were mixed uniformly in a mass ratio of 1:1 to obtain CNC-NH2 / Cu + mixture;

[0054] (3) Add 12.8 g of PVDF particles into the PEG solution and stir evenly to obtain a PVDF membrane solution;

[0055] The PEG solution was prepared by adding 3.2 g of PEG (polyethylene glycol) to 83.79 g of NMP (N-methylpyrrolidone);

[0056] (4) 0.2048 g CNC-NH2 / Cu + The mixture was added into the above PVDF membrane solution for ultrasonic dispersion, wherein CNC-NH2 / Cu +The mixture accounts for 1.6% of PVDF by mass, and then heated to 50°C and stirred for 28 hours to obtain a casting solution; the casting solution is coated on a glass plate, wherein the coating is performed using an adjustable coating device, and the flow thickness of the film is controlled by adjusting the liquid discharge speed of the adjustable coating device. The coating thickness in this embodiment is 200um. Then it is placed in pure water for phase inversion to obtain a modified PVDF membrane (1.6wt% CNC-NH2 / Cu + -PVDF).

[0057] Embodiment 5:

[0058] (1) Add 4.25 g of copper acetate into 100 ml of pure water and stir at 200 r / min until completely dissolved to obtain a 0.02 mol / L copper salt aqueous solution;

[0059] Then add 0.1 mol / L glucosamine (C6H 13 NO5) 2ml to form a glucosamine-nitric acid mixed solution, add 0.5mol / L KOH solution under stirring to adjust the pH of the mixed solution to 8; then add 2ml of 0.005mol / L reducing agent L-ascorbic acid solution dropwise to carry out reduction reaction, let stand, take the precipitate, wash and dry to obtain NH2 / Cu + Composite materials;

[0060] The washing process was to first use anhydrous ethanol to centrifuge at a speed of 8000r / min for 10 minutes, then pour out the supernatant, add anhydrous ethanol again for washing (repeat 3 times), and then wash with pure water 3 times under the same conditions. After washing, let it stand for 30 minutes, pour out the excess liquid and put it into a vacuum drying oven at 40℃ for 12 hours to obtain NH2 / Cu + Composite materials.

[0061] (2) NH2 / Cu + The composite material and CNC were mixed uniformly in a mass ratio of 1:1 to obtain CNC-NH2 / Cu + mixture;

[0062] (3) Add 12.8 g of PVDF particles into the PEG solution and stir evenly to obtain a PVDF membrane solution;

[0063] The PEG solution was prepared by adding 3.2 g of PEG (polyethylene glycol) to 83.92 g of NMP (N-methylpyrrolidone);

[0064] (4) 0.256 g CNC-NH2 / Cu + The mixture was added into the above PVDF membrane solution for ultrasonic dispersion, wherein CNC-NH2 / Cu +The mixture accounts for 2.0% of PVDF by mass, and then heated to 70°C and stirred for 20 hours to obtain a casting solution; the casting solution is coated on a glass plate, wherein the coating is performed using an adjustable coating device, and the film thickness is controlled by adjusting the liquid discharge speed of the adjustable coating device. In this embodiment, the coating thickness is 200um. Then it is placed in pure water for phase inversion to obtain a modified PVDF membrane (2.0wt% CNC-NH2 / Cu + -PVDF).

[0065] Comparative Example 1:

[0066] Same as Example 1, except that CNC-NH2 / Cu is not added in step (4). + The composition of the casting solution is: PVDF 12.8g, PEG 3.2g, NMP 83.92g, that is, CNC-NH2 / Cu + The mass percentage of the mixture to PVDF is 0; the prepared membrane is recorded as PVDF.

[0067] The membranes prepared in the above Examples 1-5 and Comparative Example 1 were first stored in a pure water environment for at least 24 hours, and then the membrane flux, anti-pollution and other properties were tested respectively.

[0068] Test example 1:

[0069] Membrane flux test:

[0070] The water flux is tested using a cross-flow filtration device. The water flux is the mass of water that can pass through the membrane per unit time under a pressure of 2 bar. The unit is LMH / bar. The formula is as follows:

[0071]

[0072] In the above formula, J w is the membrane flux, Q is the mass of permeate, A is the effective area of ​​the membrane, and Δt is the measurement time.

[0073] Test results such as Figure 1 As shown, from Figure 1 It can be seen that the water flux of the membranes prepared in Examples 1-5 of the present invention is significantly higher than the water flux of the single PVDF membrane in Comparative Example 1, indicating that CNC-NH2 / Cu + The mixture can improve the hydrophilicity of the membrane surface.

[0074] In addition, from Figure 1 It can be seen that with the increase of CNC-NH2 / Cu + As the amount of the mixture increased, the water flux of the membrane increased, but the 0.6wt% CNC-NH2 / Cu +-PVDF reached the highest value (123LMH / bar), that is, the water flux of the membrane prepared in Example 2 was the highest.

[0075] Test example 2:

[0076] The membrane prepared in Example 2 and the PVDF membrane prepared in Comparative Example 1 were subjected to pollution tests for comparison.

[0077] 1. Retention rate:

[0078] By testing the TOC of the original sewage and the TOC of the effluent, the retention rate R (%) of the membrane for pollutants in the AnMBR water environment is calculated:

[0079]

[0080] Among them, C p and C f They represent the TOC concentrations in membrane effluent and raw sewage (influent), respectively, and the TOC concentration is detected by UV-visible spectrophotometry.

[0081] In this test case, the AnMBR consists of a CSTR reactor and an external flat membrane, with an MLVSS / MLSS ratio of 0.64 and a reactor operating temperature of 35±2°C. The influent is artificial synthetic wastewater with an influent COD concentration of 500 mg / L. The synthetic wastewater is composed of sucrose (C 12 H 22 O 11 ) provides the carbon source, ammonium chloride (NH4Cl) provides the nitrogen source, and potassium dihydrogen phosphate (KH2PO4) provides the phosphorus source, where C:N:P=200:5:1. The inlet pH is mainly adjusted by sodium bicarbonate (NaHCO3), and an appropriate amount of trace elements are added to meet the needs of microbial growth.

[0082] According to the test, the TOC concentration of the water entering the membrane module from the bioreactor in AnMBR is 39.18 mg / L, the TOC concentration of the effluent from the PVDF membrane is 29.39 mg / L, and the TOC concentration of the effluent from the modified PVDF membrane is 10.58 mg / L. Figure 2 The pollutant interception rates of the PVDF membrane and the modified PVDF membrane for the AnMBR water body are 25.34% and 73.28%, respectively. This indicates that the modified PVDF membrane prepared in Example 2 of the present invention exhibits better anti-pollution performance and can be used for a longer time in the AnMBR environment.

[0083] 2. Water flux:

[0084] Detection of water flux of PVDF membrane and modified PVDF membrane in AnMBR water environment: In the cross-flow filtration device, the PVDF membrane prepared in Comparative Example 1 and the modified PVDF membrane prepared in Example 2 were first compacted with pure water as the flowing liquid under a pressure environment of 2 bar for 1 hour, and then the pressure was released, and then the flowing liquid was replaced with sewage in AnMBR, that is, both membranes were applied to the AnMBR water environment, and operated continuously for 3 hours under a pressure condition of 2 bar, and the water flux of each membrane was recorded every 10 minutes.

[0085] After the AnMBR water environment pollution test, the entire test device is flushed with pure water again. After flushing for one hour, the water flux of the membrane is tested again. The pressure is the same as before, and the flux recovery ratio FRR (%) can be calculated:

[0086]

[0087] In the formula, J W2 is the filtration flux recovered after one or more filtrations, J W1 is the initial flux. The FRR of the PVDF membrane is calculated to be 33.2%, while the FRR of the modified PVDF membrane is 73.5%.

[0088] like Figure 3 As shown, the modified PVDF membrane can quickly recover more than 70% of its original flux after being rinsed with pure water, indicating that the modified PVDF membrane prepared by the present invention has low membrane pollution and is easy to recover, extending the service life of the membrane. Its application in AnMBR can extend the operation time of AnMBR, reduce the cost of membrane components, and improve the water quality of effluent.

[0089] Comparative Example 2:

[0090] Same as Example 1-5, except that no glucosamine was added in step (1), and 0.2 wt% CNC-Cu + -PVDF, 0.6wt% CNC-Cu + -PVDF, 1.0wt% CNC-Cu + -PVDF, 1.6wt% CNC-Cu + -PVDF, 2wt% CNC-Cu + -PVDF membrane.

[0091] The water flux of each membrane was tested in the same manner as in Test Example 1:

[0092] After testing, the water fluxes of the five membranes prepared in Comparative Example 2 were 43.2, 86.2, 72.3, 56.4, and 40.5 LMH / bar, respectively, which were significantly lower than the water fluxes of the modified PVDF membranes prepared in Examples 1 to 5. This is because no glucosamine was added to inhibit its oxidation tendency, so that the cuprous ions remained active during the preparation process, ensuring their lasting effect in the membrane structure.

[0093] Same as Example 2 to test 0.6wt% CNC-Cu + -Retention rate of PVDF membrane:

[0094] After testing, the 0.6wt% CNC-Cu prepared in this comparative example 2 + -PVDF membrane has a pollutant rejection rate of 42% in AnMBR water, which is significantly lower than the modified PVDF membrane prepared in Example 2, which has a pollutant rejection rate of 73.28 in AnMBR water. This is because the lack of -NH2 + protection, while Cu + It is oxidized during the actual use of the membrane, thereby reducing the composite membrane's retention rate and anti-pollution ability for water substances.

[0095] Same as Example 2 to test 0.6wt% CNC-Cu + -Flux recovery ratio of PVDF membrane:

[0096] After testing, 0.6wt% CNC-Cu + The FRR of the -PVDF membrane is 40.5%, which is significantly lower than the FRR of the modified PVDF membrane prepared in Example 2 (63.5%).

[0097] Comparative Example 3:

[0098] The same as Example 1, except that no CNC and glucosamine were added, that is, Cu2O particles were prepared in step (1), and then added into the PVDF membrane solution to prepare Cu + -PVDF membrane. According to Cu + Different addition amounts were used to prepare 0.2wt% Cu + -PVDF, 0.6wt%Cu + -PVDF, 1.0wt%Cu + -PVDF, 1.6wt%Cu + -PVDF, 2.0wt%Cu + -PVDF membrane.

[0099] The water flux of each membrane was tested in the same manner as in Test Example 1:

[0100] After testing, the water fluxes of the five membranes prepared in Comparative Example 3 were 39.7, 40.5, 46.7, 49.6, and 41.5 LMH / bar, respectively, which were significantly lower than the water fluxes of the modified PVDF membranes prepared in Examples 1-5. This is because the lack of hydrophilic substances leads to the Cu + -Water flux of PVDF membrane.

[0101] Same as Example 2 to test 1.6wt% CNC-Cu + -The PVDF membrane has a 47% rejection rate for pollutants in AnMBR water.

[0102] Same as Example 2 for testing 1.6wt% Cu + -The flux recovery ratio of the PVDF membrane was 35.6%.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified PVDF membrane, characterized in that: The following steps are involved: (1) After adding glucosamine to the copper salt aqueous solution, the pH value of the mixed solution is adjusted to 8-10; then a reducing agent is added dropwise to perform a reduction reaction to obtain NH2 / Cu + Composite materials; (2) NH2 / Cu + The composite material and CNC are mixed evenly to obtain CNC-NH2 / Cu + mixture; (3) adding PVDF particles into PEG solution and stirring evenly to obtain PVDF membrane solution; (4) CNC-NH2 / Cu + The mixture is added into PVDF membrane liquid, dispersed by ultrasonic, and then heated and stirred to obtain a casting liquid; the casting liquid is coated with a film and placed in pure water for phase conversion to obtain a modified PVDF membrane.

2. The preparation method according to claim 1, characterized in that: In step (1), the copper salt aqueous solution includes copper nitrate, copper chloride or copper acetate aqueous solution, and its concentration is 0.02-0.08 mol / L; The reducing agent is L-ascorbic acid solution; The pH value of the mixed solution is adjusted using NaOH, KOH or Na2CO3.

3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the copper salt aqueous solution, glucosamine and reducing agent is 200:20:

1.

4. The preparation method according to claim 1, characterized in that: In step (2), the NH2 / Cu + The mixed mass ratio of composite materials and CNC is 1:

1.

5. The preparation method according to claim 1, characterized in that: In step (3), the PEG solution is obtained by adding PEG (polyethylene glycol) into NMP (N-methylpyrrolidone), wherein PEG accounts for 2-4% of the total mass of the PVDF membrane solution.

6. The preparation method according to claim 1, characterized in that: In step (4), the heating and stirring is performed at a temperature of 50-70° C. and for a time of 20-28 hours.

7. The preparation method according to claim 1, characterized in that: The CNC-NH2 / Cu + The mass ratio of the mixture to the mass ratio of PVDF is 0.2-2.0%.

8. The modified PVDF membrane obtained by the preparation method according to any one of claims 1 to 7.

9. The use of the modified PVDF membrane according to claim 8, characterized in that: It is used as an ultrafiltration membrane in AnMBR reactor for sewage filtration.

Citation Information

Patent Citations

  • Preparation method of functionalized carbon nanometer tube / metal complex anti-fouling agent

    CN103524755A

  • Antibacterial and antifouling oil-water separation material and preparation method thereof

    CN106110901A

  • Preparation method of indigotic dyeing antibacterial textile

    CN110656510A

  • New method for regulating and controlling membrane combined pollution based on synergistic effect of nano materials

    CN112619428A

  • Preparation and application of antifouling agent with characteristic of controllable release of cuprous ions

    CN112940555A